Proximal Fibular Autograft Reconstruction after Resection Giant Cell Tumor Distal Fibula - Mujaddid Idulhaq; Muhammad Luthfi Azizi (Journal Orthopaedi and Traumatology Surabaya)
Background: Giant cell tumor (GCT) is a destructive bone tumor. The predilection of the GCT is mostly on the epiphysial of long bones. GCT of the distal fibula is a very rare case that becomes challenging in surgical management. The chosen surgical management is crucial and still under debate.